2010
DOI: 10.4103/0019-5049.63650
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of basic life support among medical, dental, nursing students and doctors

Abstract: To study the awareness of Basic Life Support (BLS) among students, doctors and nurses of medical, dental, homeopathy and nursing colleges. A cross-sectional study was conducted by assessing responses to 20 selected basic questions regarding BLS among students, doctors and nurses of medical, dental, homeopathy and nursing colleges. After excluding the incomplete response forms the data was analysed on 1,054 responders. The results were analysed using an answer key prepared with the use of the Advanced Cardiac L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
150
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(179 citation statements)
references
References 4 publications
22
150
1
6
Order By: Relevance
“…In the present study, a large number of the respondents (51.3%) were reluctant to perform CPR to a stranger because they are not aware of the procedure and about one-third of them (30.1%) indicated that the reason for reluctance is being afraid of causing further harm to the patient, which is comparable to the responses of participants in a study by Alotaibi et al 7 Only 23.2% of the responders answered the rate of chest compression as 100/minute in adults and children in the present study when compared with 35% of the responders in a study by Chandrasekaran et al, 12 with the study group comprising medical, dental, nursing students, and faculty in a city in Tamil Nadu. More than half of the participants (55.2%) did not know that the right location of chest compression is the midchest in the present study, whereas 74% participants did not know the correct location of chest compression in a study by Chandrasekaran et al 12 The present study results demonstrated that 83.6% participants were not aware about the immediate action to be taken if they found someone unresponsive in the middle of the road, whereas 89% failed to insist on activating EMS immediately after confirming the unresponsiveness in an adult in a study by Chandrasekaran et al 12 The reasons for this could be multifactorial, either their lack of basic knowledge of BLS or ignorance or lack of confidence in answering this question. The present study revealed that 62.2% of the participants were not aware of Heimlich maneuver.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, a large number of the respondents (51.3%) were reluctant to perform CPR to a stranger because they are not aware of the procedure and about one-third of them (30.1%) indicated that the reason for reluctance is being afraid of causing further harm to the patient, which is comparable to the responses of participants in a study by Alotaibi et al 7 Only 23.2% of the responders answered the rate of chest compression as 100/minute in adults and children in the present study when compared with 35% of the responders in a study by Chandrasekaran et al, 12 with the study group comprising medical, dental, nursing students, and faculty in a city in Tamil Nadu. More than half of the participants (55.2%) did not know that the right location of chest compression is the midchest in the present study, whereas 74% participants did not know the correct location of chest compression in a study by Chandrasekaran et al 12 The present study results demonstrated that 83.6% participants were not aware about the immediate action to be taken if they found someone unresponsive in the middle of the road, whereas 89% failed to insist on activating EMS immediately after confirming the unresponsiveness in an adult in a study by Chandrasekaran et al 12 The reasons for this could be multifactorial, either their lack of basic knowledge of BLS or ignorance or lack of confidence in answering this question. The present study revealed that 62.2% of the participants were not aware of Heimlich maneuver.…”
Section: Discussionsupporting
confidence: 76%
“…Though, different measures of BLS/ACLS guidelines were used in similar studies, the mean score of respondents in the current study was comparable to 41.6% in a previous South-Indian study by Aroor et al [5] and marginally higher compared to 36.05% in a study of Indian dentists by Baduni et al [6] The mean score was comparable to a Nepalese study by Roshana et al [7] (44%). A greater than 50% score was achieved by 48.6% of the participants in our study, compared to <25% in the South African study by Raghavan et al [8] and South-Indian study by Chandrasekharan et al [4] (15.18%). Participants of this study also had better scores compared to a recent study on knowledge of BLS/ACLS among medical students and interns in New Delhi, India by Sinha et al [9] It should be noted that only 4.3% of the participants in our study surpassed the >80% standard set by AHA.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies were mostly done among interns, homeopaths, medical, nursing and dental students, who are often not directly responsible for emergency patient care. [4][5][6] Hence, the current study assessed BLS/ACLS knowledge amongst a broad sample of Keralite healthcare professionals who are directly involved in emergency care. The objective was to evaluate their current knowledge of BLS/ACLS guidelines and to suggest remedial measures to tackle any defi ciencies.…”
Section: Introductionmentioning
confidence: 99%
“…21 Chandrasekaran et al 11 conceded a study to evaluate knowledge of BLS among medical, dental, nursing students and doctors and concluded that their knowledge was incredibly poor and needed to be enhanced. Similarly, Sudeep et al 12 conducted a study to assess the awareness of BLS among candidates and teaching staff in a dental college and concluded that their knowledge should to be improved and updated.…”
Section: Discussionmentioning
confidence: 99%